Cardiovascular Complications in Autosomal Dominant Polycystic Kidney Disease - Ecder, Tevfik (Current Hypertension Reviews, 2013)
Cardiovascular complications are a major cause of morbidity and mortality in patients with autosomal dominant polycystic kidney disease (ADPKD). Hypertension is a common finding of ADPKD occurring in 50-70% of patients before the impairment of renal function. Stimulation of the renin-angiotensin-aldosterone system plays a major role in the development of hypertension in ADPKD. Hypertension is associated with an increased rate of progression to end-stage renal disease and is the most important potentially treatable variable in these patients. Left ventricular hypertrophy, a major cardiovascular risk factor, is also common in patients with ADPKD. Both hypertension and left ventricular hypertrophy play a crucial role in the development of cardiovascular complications in these patients. Furthermore, endothelial dysfunction, impaired coronary flow velocity reserve, biventricular diastolic dysfunction, increased carotid intima–media thickness, and arterial stiffness are present even in young normotensive patients with ADPKD who have well-preserved renal function. These findings suggest that cardiovascular involvement starts very early in the course of ADPKD. Intracranial and extracranial aneurysms and cardiac valvular defects are other potential cardiovascular problems in patients with ADPKD. A multifactorial approach aiming at all cardiovascular risk factors, such as hypertension, smoking, dyslipidemia and obesity is extremely important in these patients. Early diagnosis and treatment of hypertension, with drugs that block the renin–angiotensin–aldosterone system, has the potential to decrease the cardiovascular complications and slow the progression of renal disease in ADPKD.
Keywords: renin-angiotensin-aldosterone system